Penyuluhan Dismenore pada Remaja Putri di Pesantren Misbahul Ulum Kota Lhokseumawe - Nova Sumaini Prihatin; Nurmila Nurmila; Ernita Ernita; Rayana Iswani (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
In the United States, the prevalence of dysmenorrhea is estimated at 45-90%, while in Indonesia the prevalence of dysmenorrhea is 64.25%, consisting of 54.89% primary dysmenorrhea and 9.36% secondary. Dysmenorrhea is pain that is felt when adolescent girls menstruate. As a result, young women do not go to school. The aim is to increase the knowledge of young women about dysmenorrhea at the Misbahul Ulum Islamic Boarding School, Lhokseumawe City. The activity was carried out in three stages, namely assessment, counseling and evaluation. The target audience of Aliyah class young women is 50 participants. The results of the knowledge level of the majority of young women during the pretest were less, after socialization the level of knowledge of the majority of young women was good. Handling of dominant dysmenorrhea is done non-pharmacologically, by rubbing eucalyptus oil on the stomach. Pharmacological treatment by consuming drugs that reduce pain. As a result of dysmenorrhea, young women do not go to school, and interfere with learning concentration. It is hoped that young women can understand well the therapy used, for the Islamic boarding school to improve cooperative relationships with health services so that young women get extensive information about their reproductive health.